P1111Arrhythmogenic substrate detection in ischemic patients undergoing ventricular tachycardia ablation using multi-detector computed tomography: compared evaluation with cardiac magnetic resonance. (18th June 2020) - Jauregui, B; Soto-Iglesias, D; Zucchelli, G; Teres, C; Ordonez, A; Chauca, A; Penela, D; Acosta, J; Fernandez-Armenta, J; Linhart, M; Perea, R J; Doltra, A; et al.
Abstract: Background:  Cardiac magnetic resonance (CMR) is capable of accurately identifying arrhythmogenic substrate (AS), leading to longer arrhythmia-free survival when used to guide ventricular tachycardia (VT) substrate ablation procedures. However, the use of CMR may be limited in certain centers or patient subsets.  Purpose:  To evaluate the performance of multidetector cardiac computed tomography (MDCT) imaging in identifying heterogeneous tissue channels (HTCs) detected by CMR in ischemic patients undergoing VT substrate ablation. Methods:  Thirty ischemic patients undergoing both CMR and MDCT before VT substrate ablation were included. Using a dedicated post-processing software, two blinded operators, assigned either to CMR or MDCT analysis, characterized the presence of CMR- and CT-channels, respectively. CMR-channels were classified as endocardial (layers <50%), epicardial (layers ≥50%) or transmural. CMR- vs. CT-channel concordance was considered when the orientation was the same and they were located in the same AHA segment. Results:  Mean age was 69 ± 10 years; 90% were male. Mean left ventricular ejection fraction (LVEF) was 35 ± 10%. All patients had CMR-channels (n = 76), whereas only 26/30 (86.7%) had CT-channels (n = 91). Global sensitivity (Se) and positive predictive values (PPV) for detecting CMR-channels were 61.8% and 51.6%, respectively. MDCT performance improved in patients with epicardial CMR-channels (Se 80.5%), and transmural scars (Se 72.2%). In 4/11 (36%) patients with subendocardial MI, MDCT was unable to identify the AS. Conclusion:  MDCT fails to detect the presence of AS in 36% of patients with subendocardial MI and shows a modest sensitivity identifying the presence of HTCs, although its performance improves in patients with transmural scar.